PENGENALAN ALAT UKUR DIGITAL BAGI SEKOLAH SEPAK BOLA DI KOTA JAYAPURA - Octolia Togibasa; Pahala Tua Hutajulu (LPPM Uncen, 2019)
Science and technology play an important role in improving athletes performance, particularly soccer atheltes. However, limitations of science and technology implementation were still the main issues for soccer schools in Jayapura. In an attempt to overcome these issues, community service activities have been carried out, in the form of ”The Introduction of Digital Devices for Soccer Schools in Jayapura City”. The purspose of the activities was to improve the quality of soccer coaching. The type of the activities carried out were workshop and training of trainers (ToT). The activities was held on Saturday 5 November 2016 at the Emsyk Arena, Waena, Jayapura. The activities received strong support from both Batik Soocer School and Emsyk Soccer School. Moreover, both soccer schools had planned the procurement of Polar H7 digital devices in their training. The products outcome were practical manuals of the Polar H7 digital heart rate monitor. Keywords: soccer school, digital device, heart rate monitor